Formulation of Polymeric Microparticles Using Eco-Friendly Extracted Crude Fucoidans from Edible Brown Seaweed Undaria pinnatifida - Tania Ferreira-Anta; Maria Dolores Torres; Herminia Dominguez; Noelia Flórez-Fernández (Foods, 2023)
Several bioactive compounds that hold a potential interest in the food industry as phenolic compounds, polysaccharides, proteins and vitamins, among others, are present in seaweeds. Green extraction technologies are the preferred way to obtain these compounds. Pressurized hot water extraction, from 160 to 220 °C, was tested to achieve high yields of these components from the edible brown seaweed, Undaria pinnatifida. The maximum fucoidan content was recovered at 160 °C, while the phloroglucinol content and antioxidant activity were maximum at 220 °C. The possibility of encapsulating these bioactive fractions using mannitol was assessed. The highest production yield of the polymeric particles was found using the 220 °C fraction (close to 75%). In order to formulate microparticles with bioactive potential, several ratios of liquid phases were assessed, 3:1, 1:1 and 1:3 (w:w), using the liquid fractions obtained at 160 °C and 220 °C. The yield production was always above 67%, being in the 1:3 ratio (160 °C:220 °C) and close to 75%. The rheological results indicated that the presence of microparticles enhanced the apparent viscosity of the aqueous dispersions with non-Newtonian profiles, achieving the highest viscosity for those formulated with microparticles from 160 °C:200 °C (3:1).